A study on the corrosive inhibition ability of CT3 steel in 1 M HCl solution by caffeine and some characteristics of the inhibition process - Thao, Truong Thi; Phuong Lan, Hoang Thi; Thuy, Ngo Duong (Vietnam Journal of Chemistry, 2016)
Caffeine was isolated from dry green tea leaves and used as corrosion inhibitor. The aim of this paper is to study the corrosion inhibition behavior of caffeine with its different concentrations (from 0.01 g/L to 3.00 g/L) for CT3 steel in 1M HCl solution by the curve polarization measurements and surface examination studies. Experiment result showed that: as the concentration of caffeine increases, the inhibition efficiency increases; %IE max is approximately 83.27% at concentration of caffeine 3.00 g/L. The experimental data from all measurements was found to  fit well with the Langmuir caffeine adsorption isotherm. Calculated values of free energy of adsorption DGads are -14.71 kJ/mol. It shown that, the adsorption is spontaneous and consistent with the mechanism of physical adsorption. It showed that, the adsorption is spontaneous and consistent with the mechanism of physical adsorption. As temperature increase from 298 to 318 K, the inhibition efficiency is relatively stable: decrease slightly from 83.27 % down 78.50 %. Calculated values of the heat of adsorption DHads are ranged from -6.38 kJ/mol to -19.89 kJ/mol, indicating  that  the adsorption of caffeine on the surface of CT3 steel is exothermic. The increasing of activation energy  in corrosion process which presents caffeine 3.00 g/L compared to absent caffeine proved that caffeine have corrosion occurred more difficult